PRODUCT AND SERVICE INNOVATION IN ENTREPRENEURSHIP BUSINESS - Farida Akbarina; Farah Putri Wenang Lusianingrum, Refi Pratiwi (CV. Adiba Aisha Amira, 2025)
Product and service innovation is the key to success in modern business. Companies that are able to develop innovative products or services can win the hearts of consumers, gain a competitive advantage, and remain relevant in an ever-changing market. Therefore, it is important for companies to prioritize innovation in their business strategies and involve employees in efforts to create new ideas that can produce better products and services. With continuous innovation, companies can build a brighter future in an ever-evolving business world. The method used is a literature review using an understanding of previous research data sourced from journal references on the internet relating to product and service innovation in entrepreneurial business. Based on this study, it was found that apart from product innovation, increasing consumer repurchase interest can be done by building good service quality. Each company operating in a different field will follow its own product development strategy.